Immunophenotyping schizophrenia subtypes stratified by antipsychotic response - Li, Yanhui; Ong, Jocelyn Wen Xin; See, Yuen Mei; Yee, Jie Yin; Tang, Charmaine; Zheng, Shushan; Ng, Boon Tat; Lee, Bernett Teck Kwong; Rotzschke, Olaf; Andiappan, Anand Kumar; Lee, Jimmy (Brain, behavior, and immunity, 2025)
•Schizophrenia patients and healthy controls have immunophenotypic differences.•Differences trend across varying degrees of antipsychotic resistance.•Findings support potential immune dysregulation in treatment resistance.•CD4/CD8 ratio is a potential biomarker for antipsychotic resistance. Immune dysfunction has been proposed to play a role in the pathophysiology behind the development and persistence of psychosis. Current immunophenotyping studies are limited by small sample sizes and the number of immune markers investigated. Pharmacological subtypes in schizophrenia based on antipsychotic response have been proposed, but few studies have investigated immunophenotypes in treatment-resistant schizophrenia. In this study, we perform comprehensive immunophenotyping on 196 subjects comprising 147 schizophrenia patients stratified by antipsychotic response (49 antipsychotic-responsive, 70 clozapine-responsive, 28 clozapine-resistant) and 49 healthy controls. We aim to identify significant immune cell populations associated with schizophrenia and increasing treatment resistance, as potential modulators of underlying psychosis and/or treatment response. Patients with schizophrenia were recruited and assessed on the Clinical Global Impression – Schizophrenia (CGI-SCH). Treatment response was defined as a rating of three (mild severity) or less on the CGI-SCH positive symptom item after at least 8 weeks of adequate antipsychotic or clozapine treatment. Peripheral blood mononuclear cells were collected and flow cytometry was performed to identify 66 immune cell populations. Differences in cell population proportions were compared between schizophrenia cases and controls, and across all 4 groups, with post-hoc pairwise comparisons. Mucosal-associated invariant T (MAIT) cells (specifically CD8 + and DN double-negative subsets), total, exhausted and memory CD8 + T cells, VD1 + ϒδ T cells, plasmablasts, IgG + B cells and conventional dendritic cells 2 (cDC2) were among the top cell populations downregulated in schizophrenia. We observed increased downregulation with increasing treatment resistance. Conversely, naïve and exhausted CD4 + T cells, CD4/CD8 ratio and CCR5 + CCR2 + HLA DR + Myeloid cells were found to be upregulated in schizophrenia — we observed increased upregulation with increasing treatment resistance. We show significant immunophenotypic differences between schizophrenia cases and healthy controls, and consistent trend differences across varying degrees of antipsychotic resistance. We also examined immune cell populations not previously reported in schizophrenia. Future studies may explore immune markers identified as potential biomarkers of treatment resistance, and clarify on the relationship between immunological changes and pharmacological subtypes in schizophrenia.